The Effect Of Content Marketing Tiktok @Wardahofficial On Wardah Cosmetic Buying Interest With Attention, Interest, and Desire As Intervening Variables (Case Study of TikTok Users In Bandung City) - Nabila Al Insani; Rafiah, Kurnia Khafidhatur; Sondari, Mery Citra (International Journal of Management and Business Economics, 2024)
This study aims to determine the effect of TikTok @wardahofficial account content marketing on buying interest in Wardah cosmetics with attention, interest, and desire as intervening variables in the people of Bandung City. The type of research used is explanatory research using a quantitative approach. The sample in this study were TikTok users who live in Bandung City and have seen TikTok @wardahofficial content marketing at least once and were not scanned from May to June 2024. The data processing and analysis technique used is SEM (Structural Equation Model) using SMARTPLS (Partial Least Square) version 4.1.0.3 tools. The results of this study indicate that TikTok @wardahofficial content marketing has a positive and significant effect on buying interest in Wardah cosmetics, TikTok @wardahofficial account content marketing has a positive and significant effect on buying interest in Wardah cosmetics with attention as an intervening variable, TikTok @wardahofficial account content marketing has a positive and significant effect on buying interest in Wardah cosmetics with interest as an intervening variable and TikTok @wardahofficial account content marketing has a positive and significant effect on buying interest in Wardah cosmetics with desire as an intervening variable